An investigation into role of Server Virtualization as a tool for sustaining competitive advantage and facilitating organization effectiveness-A conceptual analysis with reference to IT industry (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This paper examines how VMware virtualization software reduces total cost of ownership (TCO) in server environments and provides almost immediate return on investment (ROI). It also demonstrates how Virtualization technology is a leading solution and why IT Industries are adopting it. Following Paper depicts a conceptual study towards the Server Virtualization technology and its advantages for any organization using the same. Various researches show that the Organization using Virtualization to optimize their server's performance and efficiency results reduced overall cost and downtime.Thus this paper will help organizations in identifying the basic benefits server virtualization technology has over other and how economy, cost benefit and effectiveness can be generated.